Pengaruh Metode Hypnoteaching Terhadap Minat Belajar Siswa Kelas 5 Sekolah Dasar - Agnes M. Goni (Peneliti.net, 2022)
The purpose of this study was to determine whether the Hypnoteacing Method Affects the Learning Interest of Grade V Students at SDN II Tomohon, Matani, Tomohon Tengah Sub-district, and to find out how much influence the Hypnoteacing Method has on the Learning Interest of Grade V students at the State Elementary School II Tomohon. This study uses a questionnaire consisting of questions that are used to collect data related to the Social Competence variable. Documentation method is used to retrieve data about learning achievement which can be seen from the value of learning outcomes in the form of values ​​from report cards. The implementation of direct learning in class V of the State Elementary School 2 Kakaskasen Tomohon City was considered good before the Covid19 Pandemic. In fact, all indicators are in the good category. The highest indicator in the application of the direct learning model is 'Providing training and guidance' with an average score of 4.18. while the indicator with the lowest score of 3.47 is 'the existence of education'. Students' learning motivation is in the good category in participating in direct learning, this is evidenced by all the indicators in the good category. The highest indicator on the variable of learning motivation of fifth graders at the State Elementary School II Kakaskasen Tomohon City is 'the desire and desire to succeed' with an average value of 4.10 and the lowest variable is Diligent in carrying out tasks' with an average value of 3.49. The application of the direct learning model has a positive and significant effect on increasing the learning motivation of grade V students at the State Elementary School 2 Kakaskasen, Tomohon City in mathematics.